HUBUNGAN ANTARA DERAJAT HIPERTENSI DENGAN KUALITAS TIDUR PADA PASIEN HIPERTENSI DI RUMAH SAKIT PMI KOTA BOGOR - Yusmahenry Galindra; Andi Asda Astiah; Naila Syahla Nuralyfah (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: According to the Ministry of Health (2021), Hypertension or high blood pressure is characterized by an increase in systolic blood pressure exceeding 140 mmHg and diastolic blood pressure exceeding 90 mmHg in two measurements taken five minutes apart in a sufficiently rested/quiet state. Poor sleep quality occurs due to increased cortisol hormone, caused by the activation of the sympathetic nervous system, which enhances vasoconstrictor effects (epinephrine and norepinephrine) that influence the increase in blood pressure. Individuals with good sleep quality tend to experience a better quality of life. This study aims to determine the relationship between the degree of hypertension and sleep quality in hypertensive patients at PMI Hospital Bogor City in 2023. Method: This is a quantitative study with a cross-sectional analytical study design. The sampling technique used in this study is non-probability sampling with a sample size of 82 individuals using accidental sampling. Sleep quality was measured using the PSQI questionnaire. Data analysis employed univariate and bivariate analyses with the chi-square statistical test. Results: The Chi-square test analysis for the relationship between the degree of hypertension and sleep quality in hypertensive patients yielded a p-value of 0.115 (p > 0.05). Conclusion: Based on the results of this research, it is concluded that there is no significant relationship between the degree of hypertension and sleep quality in hypertensive patients at PMI Hospital Bogor City in 2023. Keywords: Hypertension Severity; Sleep Quality; PSQI